Immobilized Osteopontin Enhances Adhesion but Suppresses Cytokine Release of Anti-IgE Activated Human Mast Cells - Ng, Chun Wai; Tam, Issan Yee San; Sam, Sze Wing; Yu, Yangyang; Lau, Hang Yung Alaster (Frontiers in Immunology, 2018)
Osteopontin (OPN) is an Arg-Gly-Asp (RGD)-containing extracellular matrix protein which is upregulated in inflamed tissues and has been reported to modulate mast cell activities in mice. Due to the known heterogeneity among mast cells of different species and the important roles of mast cells in allergic reactions, we investigated the effects of human OPN (hOPN) on human mast cell activities. Mature primary human cultured mast cells (HCMC) were derived from peripheral blood CD34+ progenitors and the modulation of their activation by soluble and plate-bound immobilized hOPN were examined by studying their release of inflammatory mediators (histamine, IL-5, IL-8, TNF-α and VEGF) and matrix adhesion following stimulation by anti-IgE. Immobilized hOPN enhanced the adhesion but suppressed the release of IL-5, IL-8 and TNF-α of anti-IgE-activated HCMC while soluble hOPN failed to demonstrate any significant effects. By employing cyclic RGD peptide and neutralizing antibodies against different classes of integrin and CD44, we demonstrated that the interaction of immobilized hOPN and HCMC was mediated by the RGD domain of hOPN and integrin but not CD44 on HCMC. Our results suggest that immobilized hOPN anchored to extracellular matrix can regulate adaptive immunity in humans by retaining mast cells at the site of inflammation and suppressing anti-IgE-induced cytokine release from HCMC.